Preparation method and application of solid electrolyte based on thermal amorphization
The amorphous solid electrolyte is prepared by thermal amorphization method and coated in situ on the surface of the positive electrode material, which solves the problem of increased interface impedance between the solid electrolyte and the positive electrode particles, and achieves the improvement of battery performance stability and the convenience of mass production.
Patent Information
- Application Number
- CN202510084132.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-15
AI Technical Summary
The chemical reactions and volume changes of solid electrolytes in existing all-solid-state lithium-ion batteries in electrochemical processes lead to an increase in the impedance with the positive electrode particles at the interface, affecting the stability of the electrochemical performance of the battery.
A solid electrolyte preparation method based on thermal amorphization is adopted, and an amorphous solid electrolyte is generated by grinding and mixing aluminum oxide and lithium chloride and heat treatment, and an amorphous solid electrolyte coating is formed on the surface of the positive electrode material in situ.
It realizes the simple synthesis of electrolytes in large batches and uniform coating of the cathode material, improves the cycle life and electrochemical stability of the cathode material of the battery, and is simple to operate, mild conditions, and does not produce toxic waste gas.
Smart Images

Figure CN119833638A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to battery technology, and in particular to a method for preparing a solid electrolyte based on thermal amorphization and application thereof. Background Art
[0002] With the rapid development of lithium-ion batteries, in order to obtain higher battery capacity and safer use environment, improving the energy density of lithium-ion batteries has gradually become a research hotspot. All-solid-state lithium-ion batteries use inorganic fast ion conductors such as ion-conducting polymers, oxides, and sulfides as solid electrolytes (SSEs) to replace the liquid electrolytes of traditional lithium-ion batteries. They can greatly improve the energy density of batteries while increasing the safety of the battery system, and have become the current research direction of energy storage materials. Solid electrolytes are the core of all-solid-state lithium-ion batteries and determine the capacity and stability of batteries. However, due to the chemical reactions and volume changes of solid electrolytes during the electrochemical process, the impedance at the interface with the positive electrode particles increases, which is an important cause of the electrochemical performance degradation of lithium-ion batteries.
[0003] In the field of all-solid-state battery technology, amorphous solid electrolytes have become ideal components in composite positive electrodes due to their good interface compatibility, but the current relevant synthesis methods have not yet met expectations, and usually require the generation of toxic waste gas or multiple steps of mechanical grinding. CN202311670149 discloses a surface amorphous oxygen-containing solid electrolyte and a preparation method thereof. The first step is to mix the crystalline oxygen-containing solid electrolyte body particles with a solvent and then perform a first sand milling treatment to obtain a submicronized crystalline oxygen-containing solid electrolyte body slurry; the second step is to pretreat the above-mentioned submicronized crystalline oxygen-containing solid electrolyte body slurry under the action of a pretreatment agent; the third step is to mix the pretreated crystalline oxygen-containing solid electrolyte slurry body with an amorphous additive and then perform a second sand milling treatment to obtain a surface amorphous oxygen-containing solid electrolyte.
[0004] Although this method can produce amorphous solid electrolytes, it has the problems of complicated steps, high cost, and difficulty in batch processing. In addition, since it involves a liquid phase treatment process, it is not suitable for all-solid-state battery production lines.
[0005] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0006] The main purpose of the present invention is to overcome the defects existing in the above-mentioned background technology and provide a method for preparing a solid electrolyte based on thermal amorphization and its application.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a solid electrolyte based on thermal amorphization comprises the following steps:
[0009] S1: using aluminum oxide and lithium chloride as raw materials, grinding and mixing to obtain a precursor;
[0010] S2: heat-treating the precursor, and aluminum oxide and lithium chloride react to generate an amorphous solid electrolyte.
[0011] Furthermore, the aluminum oxide includes one or more of Al2O3, LiAlO2, and Li5AlO4, and the lithium chloride includes one or more of Li3InCl6, Li2ZrCl6, and LiAlCl4.
[0012] Furthermore, the mass ratio of the aluminum oxide to the lithium chloride is (0.2-3):1.
[0013] Furthermore, the heat treatment process includes: starting from room temperature, the heating rate is 5°C / min, keeping at 150-200°C for 3-24h, and then naturally cooling to room temperature.
[0014] Furthermore, the particle size of the amorphous solid electrolyte is 1-10 μm.
[0015] An application of a thermally amorphized solid electrolyte in in-situ coating of a positive electrode comprises the following steps:
[0016] S1: using a positive electrode material containing an aluminum oxide coating layer and lithium chloride as raw materials, grinding and mixing to obtain a precursor;
[0017] S2: heat-treating the precursor, and reacting the aluminum oxide and the lithium chloride to obtain a positive electrode having an amorphous solid electrolyte layer on the particle surface.
[0018] Furthermore, the aluminum oxide includes one or more of Al2O3, LiAlO2, and Li5AlO4, and the main body of the positive electrode material includes LiNiO2, LiNi 1-x Al x O2, LiCoO2, LiNi 1-x-y Co x Mn y O2, wherein the lithium chloride comprises one or more of Li3InCl6, Li2ZrCl6, and LiAlCl4.
[0019] Furthermore, the mass ratio of the lithium chloride to the positive electrode material containing the aluminum oxide coating layer is not less than 1:10.
[0020] Furthermore, the heat treatment process includes: starting from room temperature, the heating rate is 5°C / min, keeping at 150-200°C for 3-24h, and then naturally cooling to room temperature.
[0021] Furthermore, the thickness of the amorphous solid electrolyte layer is 5-20 nm.
[0022] The present invention has the following beneficial effects:
[0023] The present invention provides a solid electrolyte preparation method based on thermal amorphization and its application, which can realize large-scale synthesis of electrolytes and in-situ coating of battery positive electrode interfaces. For electrolyte synthesis, a large number of amorphous solid electrolytes can be simply synthesized; for in-situ coating of battery positive electrodes, a uniform and thickness-controllable amorphous solid electrolyte coating layer can be formed in-situ on the surface of micron-sized positive electrode particles, thereby improving the cycle life and electrochemical stability of battery positive electrode materials. Compared with the synthesis method for achieving amorphization in the prior art, the method of the present invention is simple to operate, mild in conditions, no toxic waste gas is generated, and the atomic utilization rate is high, which is convenient for large-scale production and synthesis.
[0024] The present invention has the following two advantages:
[0025] (1) The present invention provides a method for preparing a solid electrolyte based on thermal amorphization, wherein aluminum oxide and lithium chloride are simply ground and mixed, and the temperature is raised to provide reaction energy to promote amorphization transformation. The method has a simple and convenient preparation process, mild conditions, and no volatiles are generated, which is conducive to mass production. The amorphous solid electrolyte has the characteristics of high ionic conductivity and high electrochemical stability.
[0026] (2) The present invention provides a method for in-situ generating an amorphous solid electrolyte coating layer on the surface of a positive electrode material, thereby in-situ generating an effective coating layer with high ionic conductivity and high stability during the preparation of a composite positive electrode, thereby enhancing the cycle life and safety of lithium-ion batteries of positive electrode materials coated with solid electrolytes.
[0027] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a flow chart of the synthesis of an amorphous solid electrolyte according to an embodiment of the present invention.
[0029] Figure 2 TEM characterization of the amorphous solid electrolyte synthesized in the embodiment of the present invention.
[0030] Figure 3 Comparison of electrochemical performance before and after coating with the amorphous solid electrolyte synthesized by the embodiment of the present invention. DETAILED DESCRIPTION
[0031] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0032] In view of the problems of complicated process, waste gas generation and low atomic utilization rate in the prior art for synthesizing amorphous solid electrolytes, the present invention provides a method for preparing amorphous solid electrolytes based on simple heat treatment, and the process is as follows: Figure 1 As shown, a method for preparing a solid electrolyte based on thermal amorphization comprises the following steps:
[0033] Step S1: grinding and mixing aluminum oxide and lithium chloride as raw materials to obtain a precursor. Specifically, in this step, the precursor can be obtained by weighing in proportion and grinding and mixing manually in a glove box.
[0034] Step S2: heat-treating the precursor, and aluminum oxide and lithium chloride react to generate an amorphous solid electrolyte. Specifically, in this step, the precursor can be placed in a crucible, and heated in a muffle furnace to obtain a product containing an amorphous solid electrolyte. Preferably, the particle size of the generated amorphous solid electrolyte is 1-10 μm.
[0035] In a preferred embodiment, the aluminum oxide includes one or more of Al2O3, LiAlO2, and Li5AlO4, and the lithium chloride includes one or more of Li3InCl6, Li2ZrCl6, and LiAlCl4. The mass ratio of the aluminum oxide to the lithium chloride is (0.2-3):1.
[0036] In a preferred embodiment, the heat treatment process includes: starting from room temperature, heating at a rate of 5°C / min, maintaining at 150-200°C for 3-24h, and then naturally cooling to room temperature.
[0037] The embodiment of the present invention further provides an application of a thermally amorphized solid electrolyte in an in-situ coating of a positive electrode, comprising the following steps:
[0038] Step S1: grinding and mixing the positive electrode material containing the aluminum oxide coating layer and lithium chloride as raw materials to obtain a precursor. Specifically, this step can be carried out by weighing in proportion and manually grinding and mixing in a glove box to obtain a precursor.
[0039] Step S2: heat-treating the precursor, reacting aluminum oxide and lithium chloride, and obtaining a positive electrode with an amorphous solid electrolyte layer on the particle surface. Specifically, in this step, the precursor can be placed in a crucible, and heated in a muffle furnace to obtain a positive electrode with an amorphous solid electrolyte on the particle surface. Preferably, the thickness of the generated amorphous solid electrolyte layer is 5-20nm.
[0040] In a preferred embodiment, the aluminum oxide includes one or more of Al2O3, LiAlO2, and Li5AlO4, and the main body of the positive electrode material includes LiNiO2, LiNi 1-x Al x O2, LiCoO2, LiNi 1-x-y Co x Mn y O2, the lithium chloride includes one or more of Li3InCl6, Li2ZrCl6, LiAlCl4. The mass ratio of the lithium chloride to the positive electrode material containing the aluminum oxide coating layer is not less than 1:10. The lithium chloride is in excess, mainly mixed evenly, and the mass ratio of the lithium chloride to the positive electrode material containing the aluminum oxide coating layer is not less than 1:10, preferably 3:7.
[0041] In a preferred embodiment, the heat treatment process includes: starting from room temperature, heating at a rate of 5°C / min, maintaining at 150-200°C for 3-24h, and then naturally cooling to room temperature.
[0042] Compared with the amorphous synthesis method in the prior art, the method of the present invention provides reaction activation energy for aluminum oxide and lithium chloride by heating treatment to generate an amorphous solid electrolyte, which is simple to operate, has no solution process, no harmful gas generation, high atom economy, and is convenient for mass production and synthesis. In addition, the present invention can also be used for positive electrode coating, by in-situ forming a uniform and thickness-controllable amorphous solid electrolyte coating layer, to improve the cycle life and electrochemical stability of the coated positive electrode material.
[0043] The specific embodiments of the present invention are further described below.
[0044] A method for preparing an amorphous solid electrolyte based on simple heat treatment, the process is as follows Figure 1 As shown, it includes the mixing of aluminum oxide and lithium chloride raw materials and the heating process. The method specifically includes: in a glove box, after grinding and mixing aluminum oxide and lithium chloride, a uniformly mixed mixture is obtained, wherein the ratio of the two should be between 0.2-3. Place it in a muffle furnace for heating reaction. Set the temperature change parameters as follows: start heating from room temperature, the heating rate is 5°C / min, then keep warm for 3-24h, and finally cool naturally to room temperature. The above heat treatment can provide reaction energy for amorphous transformation and promote the process of amorphous transformation. TEM test was performed on the synthesized amorphous solid electrolyte, see Figure 2 , shows the TEM characterization of the amorphous solid electrolyte particles synthesized by heating. Obvious amorphous regions can be observed, and the distribution of aluminum, oxygen, and chlorine elements can be determined from EELS, proving that the reaction occurs.
[0045] A method for in-situ forming an amorphous solid electrolyte on the surface of a positive electrode, thereby obtaining a composite positive electrode coated with an amorphous electrolyte and improving the electrochemical performance of the positive electrode material. The method specifically comprises: using a positive electrode LiNi containing an aluminum oxide coating layer 0.97 Al 0.03 O2 and Li3InCl6 were mixed (mass ratio of 70:30) and ground for 30 minutes. The composite positive electrode was placed in a muffle furnace for heating reaction, and the temperature change parameters were set as follows: heating from room temperature, heating rate of 5°C / min, then keeping warm for 3-24 hours, and finally cooling naturally to room temperature. The heat-treated composite positive electrode was used for all-solid-state battery assembly, and the electrochemical performance test was performed after standing for 4 hours. The test environment was 25°C, the voltage range was 2.2-3.7V, and the cycle test conditions were 0.2C charge and discharge cycles.
[0046] It should be noted that the present invention includes but is not limited to LiNi 1-x Al x O2 positive electrode material, and also applicable to other positive electrode materials, such as LiNi 0.8 Co 0.1 Mn 0.1 O2. The present invention is not limited to the thickness or proportion of the aluminum oxide coating layer.
[0047] Example 1
[0048] 2.4384 g of lithium chloride Li3InCl6 and 0.4614 g of aluminum oxide LiAlO2 (molar ratio 1:1) were mixed and ground for 30 min to obtain a mixture precursor.
[0049] The above mixture was placed in a muffle furnace, the heating rate was set to 5°C / min, the temperature was raised from room temperature to 150°C, and the mixture was kept at this temperature for 3 hours and then cooled to room temperature.
[0050] Example 2
[0051] The materials used are the same as those in Example 1, except that the molar ratio of Li3InCl6 to LiAlO2 is 1:3, and the other preparation conditions are the same.
[0052] Example 3
[0053] The materials used are the same as those in Example 1, except that the molar ratio of Li3InCl6 to LiAlO2 is 1:0.5, and the other preparation conditions are the same.
[0054] Example 4
[0055] The materials used are the same as those in Example 1, except that the molar ratio of Li3InCl6 to LiAlO2 is 1:0.2, and the other preparation conditions are the same.
[0056] Example 5
[0057] The material ratio is the same as that in Example 1, except that the heating time is 24 hours, and other preparation conditions are the same.
[0058] Example 6
[0059] The material ratio is the same as that in Example 1, except that the heating temperature is 200° C. and other preparation conditions are the same.
[0060] Example 7
[0061] The heating conditions are the same as those in Example 1, except that the materials used are Li2ZrCl4 and LiAlO2 with a molar ratio of 1:1.
[0062] Example 8
[0063] The heating conditions are the same as those in Example 1, except that the materials used are LiAlCl4 and LiAlO2, with a molar ratio of 1:1.
[0064] Example 9
[0065] The heating conditions are the same as those in Example 1, except that the material used is LiAlO2-coated LiNi 0.97 Al 0.03 O2 positive electrode and Li3InCl6. The electrochemical cycle performance of the positive electrode before and after treatment is as follows Figure 3 shown.
[0066] Figure 3 In the figure, the blue part shows the electrochemical performance of the positive electrode assembled all-solid-state battery without heat treatment, and the red part shows the electrochemical performance of the positive electrode assembled all-solid-state battery treated at 150°C. Figure 3 (a), (b), and (c) are comparisons of electrochemical performance before and after treatment at rates of 0.2C, 0.5C, and 1C, respectively. It can be seen that the discharge capacity (red) after treatment at each rate is significantly better than the discharge capacity (blue) before treatment, and the difference is greater at high rates, and the performance improvement is more significant. The results show that the treatment of the present invention can improve the discharge capacity of the positive electrode, and the improvement effect is more significant at long cycles and high rates.
[0067] In summary, the present invention provides a method for preparing a solid electrolyte based on thermal amorphization and its application. A heat treatment is used to provide reaction activation energy for aluminum oxide and lithium chloride to generate an amorphous solid electrolyte. Compared with the amorphous synthesis method in the prior art, the method of the present invention is simple to operate, has no solution process, no harmful gas generation, high atom economy, and is convenient for mass production and synthesis. In addition, the method can also be used for positive electrode coating, by in-situ forming a uniform and thickness-controllable amorphous solid electrolyte coating layer, thereby improving the cycle life and electrochemical stability of the coated positive electrode material.
[0068] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, they can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the scope of protection of the present invention. In the description of this specification, the reference terms "one embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" refer to the specific features, structures, materials or characteristics described in combination with the embodiment or example. At least one of the present invention In this specification, the above terms are used to illustrate The statements do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. Those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradicting each other. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications may be made herein without departing from the scope of protection of the patent application.
Claims
1. A method for preparing a solid electrolyte based on thermal amorphization, characterized in that: The following steps are involved: S1: using aluminum oxide and lithium chloride as raw materials, grinding and mixing to obtain a precursor; S2: heat-treating the precursor, and aluminum oxide and lithium chloride react to generate an amorphous solid electrolyte.
2. The method for preparing a solid electrolyte based on thermal amorphization according to claim 1, characterized in that: The aluminum oxide includes one or more of Al2O3, LiAlO2, and Li5AlO4, and the lithium chloride includes one or more of Li3InCl6, Li2ZrCl6, and LiAlCl4.
3. The method for preparing a solid electrolyte based on thermal amorphization according to claim 1 or 2, characterized in that: The mass ratio of the aluminum oxide to the lithium chloride is (0.2-3):
1.
4. The method for preparing a solid electrolyte based on thermal amorphization according to claim 1 or 2, characterized in that: The heat treatment process includes: starting from room temperature, heating at a rate of 5°C / min, maintaining at 150-200°C for 3-24h, and then naturally cooling to room temperature.
5. The method for preparing a solid electrolyte based on thermal amorphization according to claim 1 or 2, characterized in that: The particle size of the amorphous solid electrolyte is 1-10 μm.
6. Application of a thermally amorphized solid electrolyte in in-situ coating of a positive electrode, characterized in that: The following steps are involved: S1: using a positive electrode material containing an aluminum oxide coating layer and lithium chloride as raw materials, grinding and mixing to obtain a precursor; S2: heat-treating the precursor, and reacting the aluminum oxide and the lithium chloride to obtain a positive electrode having an amorphous solid electrolyte layer on the particle surface.
7. The application of the thermally amorphized solid electrolyte in the in-situ coating of the positive electrode according to claim 6, characterized in that: The aluminum oxide includes one or more of Al2O3, LiAlO2, and Li5AlO4, and the main body of the positive electrode material includes LiNiO2, LiNi 1-x Al x O2, LiCoO2, LiNi 1-x-y Co x Mn y O2, wherein the lithium chloride comprises one or more of Li3InCl6, Li2ZrCl6, and LiAlCl4.
8. The application of the thermally amorphized solid electrolyte in the in-situ coating of the positive electrode as claimed in claim 6 or 7, characterized in that: The mass ratio of the lithium chloride to the positive electrode material containing the aluminum oxide coating layer is not less than 1:
10.
9. The use according to claim 6 or 7, characterized in that The heat treatment process includes: starting from room temperature, heating at a rate of 5°C / min, maintaining at 150-200°C for 3-24h, and then naturally cooling to room temperature.
10. The use according to claim 6 or 7, characterized in that: The thickness of the amorphous solid electrolyte layer is 5-20 nm.
Citation Information
Patent Citations
Surface layer non-crystallized oxygen-containing solid electrolyte and preparation method and application thereof
CN117712468A
Lithium-rich manganese-based solid-state battery electrode and secondary battery
CN111129429A
Inorganic nano hydrophobic material doped solid electrolyte material and preparation method and application thereof
CN117154201A
purification apparatus by Sublimating an organic and non-organic material
KR1020250144707A